A comparative ontogenic study of urinary bladder: Impact of the epithelial differentiation in embryonic and newborn rats - ERCAN, FERİHA (WILEY, 2006)
The present study aimed to show the cellular and subcellular distribution of glycogen content during the differentiation of urothelial cells from simple cuboidal to stratified transitional epithelium. Bladder samples were taken from rat embryos on the 15th to 19th days and newborn at 21st day. During the development of the bladder, the formation of fusiform vesicles, asymmetric unit membrane (AUM) and microridges were examined with staining with haematoxylin-eosin and periodic acid Schiff for light microscope and periodic acid-thiocharbohydrazide-silver proteinate for transmission electron microscope. The topographical changes of luminal differentiation were examined with the scanning electron microscope. The urothelium was simple cuboidal from 15th till the 17th days of gestation. Glycogen content was present in the cytoplasm till the 18th day of gestation. At the early stage (16th day) of gestation, the apical surface contains microvilli that points the undifferentiated cells. The density of microvilli decreased and ropy microridges appeared at the 17th day of gestation. The small discoid vesicles lined with AUM developed at the apical cytoplasm of the surface cells at the 17th day of gestation. After this stage, both the density of microridges and large and elongated fusiform vesicles increased. The differentiation of the urothelium begins with the formation of the round and small vesicles, continues with the formation of the AUM and at the final stage there is a decrease in both glycogen content and the appearance of the microridges at the luminal surface of the urothelial cells.
Keywords: SMOOTH-MUSCLE; SURFACE GLYCOSAMINOGLYCANS; INTERSTITIAL CYSTITIS; PERMEABILITY BARRIER; SUPERFICIAL CELLS; GOLGI-APPARATUS; FINE-STRUCTURE; MOUSE; FETAL; STRESS